Influence of heat treatment at different time temperature combination on ice cream mix prepared with partial addition of bovine liquid colostrum - Das, Anamika; Seth, Raman (Indian Journal of Dairy Science, 2017)
Colostrum, the first secretion after parturition, is emerging as the most potent natural immune booster for human beings. Nowadays, consumers are inclined towards supplementing food to remain healthy. Colostrum is the first mammary secretion for 24 -72 hours after parturition and is a rich source of immune components, growth factors, and has enhanced level of protein, immunoglobulins (Ig), fat, vitamins, and minerals than does milk. When ice cream mix prepared with the colostrum-skim milk ratios of 30:70, 40:60 and was subjected to heat treatment at 72oC/30min, 70oC/30min and 68oC/30min, there was visible coagulation of ice cream mix.When ice cream mix prepared with different ratios of colostrum:skim milk viz. 10:90 and 20:80 was heat treated at 68oC/30min, no significant decrease in IgG and IgA concentration was observed(P>0.05) before and after heat treatment. Therefore the time temperature combination of 68oC/30min was standardised for heat treatment of ice cream mix at which it survives coagulation and has minimum denaturation of immunoglobulins alongwith a decreased microbial count.